Spatial Organization in a Rural Akkadian Farmhouse: Perspectives from Tepe al-Atiqeh, Iraq - Gnivecki, Perry Louis
Ph.D. Dissertation; Dissertation committee: W. H. Isbell (chair), A. J. Ammerman, H. A. Koster, G. E. Kadish, McGuire Gibson; Order No. DA8321233; cf. DissAbstr 44/05 (November 1983) 1501-A; Chicago-Copenhagen Expedition to the Hamrin, 1978/1979.